Antidiabetic Activity of Cep-Cepan Leaf Extract Nanoparticles (Castanopsis costata) in Streptozotocin-Induced White Rat Models - Astriani Natalia Br Ginting; Chrismis Novalinda Ginting; Gusbakti Rusip; Linda Chiuman (Postgraduate, University of Mataram, 2025)
The cep-cepan plant (Castanopsis costata) from the Fagaceae family is traditionally used by the Karo community in Medan, North Sumatra, to treat diabetes mellitus, although its efficacy has not yet been scientifically proven. This study aimed to evaluate the effectiveness of the antidiabetic activity of cep-cepan leaf extract nanoparticles (Castanopsis costata) in a streptozotocin-induced white rat model. A total of 25 male white rats were divided into five treatment groups: a positive control group, a negative control group, and three experimental groups treated with extract concentrations of 25, 75, and 150 mg/kg body weight, respectively. Plasma glucose levels were measured every 72 hours for 15 days using blood samples taken from the tail. Pancreatic tissue was then examined, and the data were analyzed using one way anova. The findings showed significant antidiabetic activity in all treatment groups, with p < 0.001. The nanoparticle extract of cep-cepan leaves exhibited the highest antidiabetic potential at a dosage of 150 mg/kg, reducing blood glucose levels by 59.39%. These results suggest that the nanoparticle extract of cep-cepan leaves demonstrates antidiabetic activity in the streptozotocin-induced white rat model, and it has the potential to be developed as an alternative treatment for diabetes mellitus.